Management of a Portobiliary Fistula and Obstructive Biliopathy in a Split Liver Graft Transplant Recipient Posthepaticojejunostomy with Portal Stent Graft - Saurabh Kumar; Apoorva Batra; Vaibhaw Kumar; Vivek Vij (Journal of Clinical Interventional Radiology ISVIR)
Biliary complications following liver transplantations, in the form of bile leak and bile duct strictures, are well recognized. Portobiliary fistulas in the transplant setting are rare, but may cause potentially life-threatening complications. The presented case shows the successful treatment of a hilar portobiliary fistula in a transplanted liver posthepaticojejunostomy with portal vein stent graft followed by biliary drainage with percutaneous hepaticojejunostomy stricture dilatation.